FORECAST ON THE CASPIAN SEA LEVEL AND ITS EFFECTS ON THE COASTAL TERRITORY - S. A. Guseinova; A. S. Abdusamadov (Юг России: экология, развитие)
The aim is to assess the dynamics of the Caspian Sea and its impacts on coastal areas as well as to develop recommendations for economic activity in a highly unstable position of the coastline.Methods. Based on the analysis of scientific sources and our own data on the dynamics of the Caspian Sea, are discussed the possible causes of the unstable regime of the sea level and its impacts on the ecological system of the coastal areas.Results. One of the problems of the Caspian Sea is the problem of sea-level change and predicting such changes. The analysis shows that the level of the Caspian Sea will continue to experience long-term (including thirty-year and secular) fluctuations in the range of absolute marks minus 26 to minus 33 m, which is close to the shoreline as in 1977.Conclusions. We find it possible to prevent the negative effects of level fluctuations, preserve biodiversity and biological resources of the Caspian Sea on condition that during the economic activities in the zone off the coast we take into account possible changes in the natural conditions of the coastal zone at risk from -20 to -34 meters of true altitude, i.e. elevations within which the sea water level will fluctuate.